Depression, anxiety and stress amongst students in science verses non-science stream: a comparative study - Chokshi, Anushka S.; Rangwala, Pooja P.; Dumra, Gurusharan H.; Thakrar, Manan R.; Singh, A. J.; Lakdawala, Bhaveshkumar M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Depression (D), anxiety (A) and stress (S) are common issues among students nowadays. The occurrence of D, A, and S was primarily considered to be associated with the students’ academics, especially in twelfth standard because these groups are highly vulnerable to immense pressure, rising competition for undergraduate courses and constant changes in the education system. The objective of this study was to find the comparative magnitude of occurrence and severity of D, A, and S in the science and non-science stream among twelfth standard students. Methods: This cross-sectional study was carried out across 460 students of twelfth standard from all streams. A socio-demographic questionnaire along with DASS-42 was distributed. The scores were calculated and percentage, mean scores, standard deviation, p values, odds ratio were obtained. Results: A statistically significant difference was seen in the mean scores of depression and anxiety among science and non-science students (p<0.005). Students belonging to science stream showed more depression and anxiety overall as well as when compared on basis of age groups. Similar results were also observed among science students who said it was not their own decision to choose their stream. Anxiety was found to be higher in science students from nuclear families where as depression was higher in those from joint family. On the contrary, occurrence of all states was found to be more in females of non-science field as compared to science field. Conclusions: Along with academic pressure, various other factors like gender, voluntary choice of stream, type of student’s family etc. contributed to D, A, and S in students.